2023
DOI: 10.7717/peerj.14926
|View full text |Cite
|
Sign up to set email alerts
|

Level of attention mediates the association between connectedness to nature and aesthetic evaluations of photographs of nature

Abstract: Aesthetic experiences of nature are associated with beneficial psychological and behavioural outcomes. We investigated in a laboratory study whether an individual’s level of connectedness to nature is associated with their aesthetic sensitivity to images of natural scenes, and whether the amount of attention allocated to the images mediated this association. Participants (N = 82) viewed 14 photographs depicting natural scenes and evaluated them on three aesthetic dimensions and completed the Connectedness to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Nature connectedness predicted image ratings and NA positively. For the image ratings, this was expected (Harrison, 2023;Menzel & Reese, 2021), but it is surprising for NA. Findings indicated that the higher their connection to nature, the higher their NA after image presentation.…”
Section: Discussionmentioning
confidence: 77%
“…Nature connectedness predicted image ratings and NA positively. For the image ratings, this was expected (Harrison, 2023;Menzel & Reese, 2021), but it is surprising for NA. Findings indicated that the higher their connection to nature, the higher their NA after image presentation.…”
Section: Discussionmentioning
confidence: 77%